Weathering behaviour of a basaltic regolith from Pahang, Malaysia - Jol, Hamdan; Mat, Peli; Busu, Ruhana (Universiti Putra Malaysia Press, 2003)
The characteristics and degree of weathering in a deep saprolitic regolith developed on basalt were investigated. A 15 m deep regolith of soil-saprolite-rock sequence, located along a new road cut in Pahang, Malaysia, was selected. The intensity of weathering in this regolith was assessed by various weathering indices, as well as by the changes in the physiarchemical properties, clay mineralogy and the microfabric characteristics of the profile. All assessments gave strong evidences of intense weathering, even at the stage of saprock formation. Extreme depletion of major elements such as K, Na, Ga and Mg, and significant enrichment of Fe, Ti, Gu and Nb occurred during saprolitization process, and, these perhaps explain the extreme weathering pattern of this regolith.